2016
DOI: 10.1149/2.0661613jes
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Critical Chemistry for Repassivation at the Corroding Surface Using Mass Transport Model-Based Artificial Pit Experiments

Abstract: One-dimensional mass transport model calculations were utilized to design experiments with stainless steel artificial pit electrodes to determine the critical concentration of cations at the corroding surface representing the transition between stable pitting and repassivation. Rapid polarization scans following salt film precipitation and consequent open circuit dilution to different surface concentrations permitted the evaluation of kinetics at various degrees of saturation. These experiments showed a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…It has been reported that surface oxides and hydroxides of Fe, Cr, and Mo atoms are abundant on the surface of 316 L stainless steel becoming more and more prominent at pH levels greater than 9. [35] We surmise that these oxides and hydroxides are likely providing the H and O atoms required to produce the observed "hydrolysis" degradation in the highly basic 1-IPADM-2-BOL.…”
Section: Assessing the Influence Of Steel Interfaces On Solvent Durabilitymentioning
confidence: 86%
“…It has been reported that surface oxides and hydroxides of Fe, Cr, and Mo atoms are abundant on the surface of 316 L stainless steel becoming more and more prominent at pH levels greater than 9. [35] We surmise that these oxides and hydroxides are likely providing the H and O atoms required to produce the observed "hydrolysis" degradation in the highly basic 1-IPADM-2-BOL.…”
Section: Assessing the Influence Of Steel Interfaces On Solvent Durabilitymentioning
confidence: 86%
“…We consider three types of electrode reactions happening during the experiment: anodic metal dissolution, internal and external cathodic reactions [41]. Anodic dissolution and the internal cathodic reaction occur on the corroding surface of the 316L stainless steel wire, which is directly exposed to sodium chloride solution.…”
Section: Electrode Reactions and Kineticsmentioning
confidence: 99%
“…The simplest of mechanistic models consider mass transport of solute species (e.g., metal or hydrogen ions) in the solution environment based on the Fick's law of diffusion [36]. Therefore, the 1-D Fickian diffusion model has been widely used to simulate the evolution of the chemistry inside the 1-D pit [37][38][39][40][41][42]. Srinivasan et al used this model to evaluate the effect of the external hemispherical boundary layer on the cation flux inside the pit [40] and to demonstrate the dilution of cations near the corroding surface when repassivation happens [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] The metastable pit growth often results in pits with lacy covers, which are able to maintain a high concentration of Cl − and a lowpH electrolyte within occluded pit cavities. [28,29] Stable pit growth is associated with a critical electrochemical potential (E pit ) or a critical pitting temperature, [30,31] and stable pits generally have a larger pit volume, with the pit depth acting as the diffusion barrier. [32,33] Bipolar electrochemistry has now become accessible for corrosion testing and screening, featuring a noncontact experimental setup, by in parallel being able to observe the full corrosion response during one single experiment.…”
Section: Introductionmentioning
confidence: 99%